Hubungan Antara Sumber dan Metode Penghitungan Kerugian Keuangan Negara dengan Penetapan Uang Pengganti - Mahrus Ali (Jurnal Hukum IUS QUIA IUSTUM, 2014)
There are two main things discussed in this research; first, the source of the state financial loss and the calculation method in the court decision of corruption case, and second,the correlation between the calculation method of the state financial loss in the legal perspective of the judges and the decision on the amount of indemnification. This research is a normative legal study. The result of the research shows that first, the source of the state financial loss varies from the asset release, fictitious activities, unsettled payables of tax payers, andout-of-budget expenses, with the calculation method used involving rounded down total loss, main loss, main loss plus interest, and the margin between the amount of the budget subtracted by the realization of the used amount. Second, in deciding the amount of the indemnification, not all of the judges referred to the calculation method of the state financial loss.